2021
DOI: 10.3389/fncel.2021.654340
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol Induces Autophagy to Protects Neural Cells From Mitochondrial Dysfunction by Upregulating SIRT1 to Inhibits NF-κB and NOTCH Pathways

Abstract: The protective effect of Cannabidiol on Parkinson’s disease (PD) has been found in recent study. However, the specific mechanism of the protective effect of Cannabidiol on PD nerve damage require further exploration. This study aims to investigate effect of Cannabidiol on MMP-induced Neural Cells (SH-SY5Y) mitochondrial dysfunction. MMP+ and Cannabidiol were used to treat SH-SY5Y cells, the cells viability was measured by MTT assay. The expression of Tyrosine hydroxylase (TH) in cells was measured by western b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 33 publications
0
16
1
Order By: Relevance
“…SIRT1 is the main regulator of neurogenesis and plays a neuroprotective role in neurological diseases [ 38 ]. Previous studies showed that activation of SIRT1 reversed nerve damage in different neurological diseases by augmenting hippocampal neurogenesis [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…SIRT1 is the main regulator of neurogenesis and plays a neuroprotective role in neurological diseases [ 38 ]. Previous studies showed that activation of SIRT1 reversed nerve damage in different neurological diseases by augmenting hippocampal neurogenesis [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The notion that SIRT1 controls mammalian cell growth and survival under stress is widely recognized; however, this effect has been reported as either a promoter or suppressor depending on the cell types studied, ranging from immortalized cell lines of various lineages to cancer cells and neural stem cells. A recent study showed that CBD induced autophagy in SH-SY5Y cells, which protected the cell from mitochondrial dysfunction by upregulating SIRT1 and inhibiting NF-KB and Notch pathways [ 59 ]. Our study showed that CBD increased neurite outgrowth and spine density via SIRT1.…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidants are the first defense to detoxify ROS [ 14 ]. Identification of effective antioxidant active chemical components from plants or natural products, eliminating active oxygen and maintaining homeostasis, is one of the hotspots of the current research [ 18 , 19 ]. NGR1 has been reported to treated neurological complications [ 8 , 9 ]; in addition, NGR1 has anti-inflammatory and antioxidative stress effects [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that NGR1 has an effect on mitochondrial dysfunction and Ca 2+ concentration. When mitochondria are damaged, activated PINK1 aggregates on the outer mitochondrial membrane and induces mitochondrial autophagy through direct/indirect activated Parkin [ 29 ], thereby protecting mitochondrial DNA from reactive oxygen species and stimulating the self-repair process of mitochondria [ 19 ]. In this study, we found that NGR1 treatment activates the PINK1/Parkin pathway and upregulates Parkin expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation